Major pathways to electron distribution function formation in regions of diffuse aurora. Issue 4 (12th April 2017) - Khazanov, George V.; Sibeck, David G.; Zesta, Eftyhia
Abstract: This paper discusses the major pathways of electron distribution function formation in the region of diffuse aurora. The diffuse aurora accounts for about of 75% of the auroral energy precipitating into the upper atmosphere, and its origin has been the subject of much discussion. We show that an earthward stream of precipitating electrons initially injected from the Earth ' s plasma sheet via wave‐particle interactions degrades in the atmosphere toward lower energies and produces secondary electrons via impact ionization of the neutral atmosphere. These electrons of magnetospheric origin are then reflected back into the magnetosphere along closed dipolar magnetic field lines, leading to a series of reflections and consequent magnetospheric interactions that greatly augment the initially precipitating flux at the upper ionospheric boundary (700–800 km). To date this, systematic magnetosphere‐ionosphere coupling element has not been included in auroral research models, and, as we demonstrate in this article, has a dramatic effect (200–300%) on the formation of the precipitating fluxes that result in the diffuse aurora. It is shown that wave‐particle interaction processes that drive precipitating fluxes in the region of diffuse aurora from the magnetospheric altitudes are only the first step in the formation of electron precipitation at ionospheric altitudes, and they cannot be separated from the atmospheric "collisional machine" that redistributes and transfers their energy inside the magnetosphere‐ionosphere‐atmosphere coupling system. Key Points: Formation of electron distribution function in the region of diffuse aurora Magnetosphere‐ionosphere coupling plays important role in the formation of diffuse aurora This paper provides a foundational theory for the diffuse aurora Plain Language Summary: It is shown that wave particle interaction processes that drive precipitating fluxes in the region of diffuse aurora from the magnetospheric altitudes are only the first step in the formation of electron precipitation at ionospheric altitudes, and they cannot be separated from the atmospheric "collisional machine" that redistributes and transfers their energy inside the magnetosphere‐ionosphere‐atmosphere coupling system.